Subjective cognitive and neurocognitive functions over the course of CBT - Bernhardt, Maren; Schwert, Christine; Aschenbrenner, Steffen; Weisbrod, Matthias; Schröder, Annette (Psychiatry research, 2021)
The aim of the study was to investigate changes in both subjectively and objectively measured cognitive functions as well as their discrepancy in outpatients with major depression disorder in the course of cognitive-behavioural therapy (CBT). A neuropsychological test battery with cognitive tests measuring the domains of attention, memory, and executive functions as well as a questionnaire for the self-assessment of cognitive functions (FLei) in these domains were administered to depressed outpatients (n = 46) at the beginning of CBT, post-treatment after on average 40 sessions, as well as six months after the end of treatment. We found that subjectively as well as objectively measured cognitive functions did not change. The discrepancy between subjective and objective cognitive functions found at the beginning of therapy was no longer significant at post-treatment and six months later. The results indicate, that self-perceived and neuropsychologically measured cognitive impairments show stability despite improved depression. Specific interventions such as cognitive remediation therapy should be additionally applied to depressed patients who suffer from cognitive deficits.